Identification and Characterization of Osmoregulation Related MicroRNAs in Gills of Hybrid Tilapia Under Three Types of Osmotic Stress - Su, Huanhuan; Fan, Jiajia; Ma, Dongmei; Zhu, Huaping (Frontiers in Genetics, 2021)
Increasingly researches have suggested that microRNAs (miRNAs) are small noncoding RNAs that post-transcriptionally regulate genes expression and protein translation in organs and also response to abiotic and biotic stressors. To understand the function of miRNAs in osmotic stress regulation of the gills of hybrid tilapia (Oreochromis mossambicus ♀ × O. urolepis hornorum ♂), high-throughput Illumina deep sequencing technology was used to investigate the expression profiles of miRNAs under salinity stress (S, 25‰), alkalinity stress (A, 4‰) and salinity-alkalinity stress (SA, S: 15‰, A: 4‰) challenged. The results showed that 31, 41 and 27 upregulated and 33, 42 and 40 downregulated miRNAs (P < 0.05) were identified in the salt stress, alkali stress and saline-alkali stress group, respectively, which were compared with those in the control group (C). 14 significant differently expressed miRNAs were selected in randomly and then validated by qPCR. On the basis of GO and KEGG pathway analysis, genes related to osmoregulation and biosynthesis were enriched in the three types of osmotic stress. In addition, three miRNAs and three predicted target genes were chose to conduct qPCR in the hybrid tilapia and its parents during 96 h osmotic stressed. Differential expression patterns of miRNAs providing basis research data for further investigation of the miRNA-modulating networks in osmoregulation of teleost.